2017
DOI: 10.1111/jfpp.13450
|View full text |Cite
|
Sign up to set email alerts
|

Process optimization of polyphenol extraction from carob (Ceratonia siliqua) kibbles using microwave‐assisted technique

Abstract: Microwave‐assisted extraction (MAE) method was investigated to recover phenolic compounds from carob kibbles and validated using response surface methodology. The study parameters were microwave power (170–900 W), ethanol concentration (30–90%), and solvent‐to‐sample ratio (10–30 mL/g) in terms of total phenolic content (TPC) and condensed tannins. Among optimized parameters (340 W, 45%, 30 mL/g), microwave power and ethanol concentration were found more influential parameters to get higher yields of TPC and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…Intracellular content is heated and evaporated, producing strong pressure. This pressure breaks the cell wall and membranes, liberating intracellular content into the solvent [59,61]. Water, methanol, and ethanol are the solvents recommended for this extraction [39].…”
Section: Microwave-assisted Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular content is heated and evaporated, producing strong pressure. This pressure breaks the cell wall and membranes, liberating intracellular content into the solvent [59,61]. Water, methanol, and ethanol are the solvents recommended for this extraction [39].…”
Section: Microwave-assisted Extractionmentioning
confidence: 99%
“…The frequency applied, ranging from 300 MHz to 300 GHz, and the microwave power, with ranges between 100 and 900 W, play a fundamental role in the extraction of tannins since their increment, usually, leads to a more efficient recovery [34,35,54]. The time needed for these extraction protocols is short, from 1 to 20 min, achieving a substantial amount of tannins (from 4.11 to 528.5 mg/g of dried extract, Table 2) [43,59,61].…”
Section: Microwave-assisted Extractionmentioning
confidence: 99%
“…Traditionally, aqueous ethanol is utilized for the recovery of polyphenol‐rich food grade extracts from plant materials (Huma, Jayasena, Nasar‐Abbas, Imran, & Khan, ). However, the use of ethanol results in the co‐extraction of high chlorophyll concentrations (Yasuda, Oda, Ueda, & Tabata, ).…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have reported that high percentages of ethanol can break the hydrogen and hydrophobic bonds existing between phenolics–proteins and phenolics–cellulose in ethanol/water solutions, improving the extraction process [ 26 ]. However, some authors have demonstrated that the presence of small amounts of water in the solvent during MAE could favour a possible diffusion of water into the matrix cells, achieving a better heating and, thus, helping the transfer of compounds into the solvent at higher mass transfer rates [ 27 ].…”
Section: Resultsmentioning
confidence: 99%